Recent advances in additive manufacturing of active mechanical metamaterials. Issue 5 (October 2020) - Montgomery, S. Macrae; Kuang, Xiao; Armstrong, Connor D.; Qi, H. Jerry
Highlights: Introducing progresses in AM technologies used to fabricate mechanical metamaterials. Highlighting unique properties of active metamaterials enabled by AM. Exploring emerging additive manufacturing methods. Discussing perspectives of AM for future active mechanical metamaterials. Abstract: Active mechanical metamaterials are emerging materials receiving tremendous attention in the past decades. Additive manufacturing (AM, or 3D printing) techniques empower the rational design and fabrication of complex, multiscale architectures that enable unprecedented mechanical properties and functionality of metamaterials. Moreover, the use of smart or stimuli-responsive materials for AM of active mechanical metamaterials offers new capabilities to program the mechanical, acoustic, or other functional properties. Herein, we present an overview of recent advances in AM of active mechanical metamaterials. The primary AM techniques used for mechanical metamaterial fabrication are discussed first. Several mechanical metamaterial structures and designs enabled by AM are summarized. Active mechanical metamaterial designs utilizing different stimuli, such as solvents, heat, and magnetic field, are introduced. Additionally, some functional applications of active material systems to create transforming mechanical metamaterials are included. Finally, the outlook and challenges for future research in this field are provided.